Pemikiran Fiqh Imam Ja’far Asshiddiq - Safriadi Nurdin (Ma'had Aly Raudhatul Ma'arif, 2023)
This research raises about the fiqh thinking of Imam Ja'far Asshiddiq (tracing the development of the ja'fariyah madhhab). In this research, the author uses library research, and data collection is done by studying books and books about Fiqh Ja'fari, ushul fiqh Ja'fariyah as primary material, and other books related to the discussion of this research as secondary material, so this pattern is qualitative. In addition, the analysis that the author uses is descriptive analysis. From the results of this research, it is concluded that Imam Ja'far Asshadiq is the founder of the Ja'fariyah school. he was born in 80 AH and died in 148 AH. The titles Imam and Shadiq were given to him because: Firstly, Imam Ja'far was known to be a truly shadiq person, truthful in his words and deeds, nothing was known from Ja'far other than the trait of shidq (honest, truthful). Secondly, because of the depth and breadth of his knowledge. The sources of law of this madhhab are the Qur'an, Sunnah, Ijma', and Reason. In terms of fiqh, this school is very close with only 17 differences with the fiqh of the sunnah experts (Hanafiyah, Malikiyah, Shafi'iyah, and Hambaliyah). One of the most important of these is the issue of legalising mut'ah marriage. Ahl as-Sunnah are all agreed that mut'ah marriage is haram and is no different from zina.